PERAN EDUKASI PEMBERDAYAAN PEREMPUAN DALAM MENINGKATKAN KEPEDULIAN LINGKUNGAN DAN PARTISIPASI KEWARGAAN DI KALANGAN MASYARAKAT DI DESA SESE - Hidayati Gabriel; Mirayanti Mirayanti; Selvi Selvi; Sandi Sandi; Jibran Febriansyah (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service aims to analyse the role of education in empowering women to increase environmental awareness and civic participation among the Sese Village community. Women's involvement in realising sustainable village development is low. Using a descriptive qualitative approach, activities were implemented in counselling, training, and mentoring for village women's groups. Data collection was conducted through interviews, observations, and documentation of activities. The study results indicate that structured and participatory education can increase women's understanding and awareness of the importance of protecting the environment and their role in social community activities, such as waste management, reforestation, and village deliberations. This education also strengthens women's roles as drivers of change in the family and the surrounding environment. Thus, women's empowerment education activities have proven effective in fostering environmental awareness and increasing civic participation, and can be used as a strategy to support participatory-based village development.